ACTH controls thymocyte homeostasis independent of glucocorticoids. Issue 6 (2nd March 2015) - Talaber, Gergely; Tuckermann, Jan Peter; Okret, Sam
ABSTRACT: It has been known for decades that lowering the circulating glucocorticoid (GC) concentration as in Addison's disease or after removing the adrenals results in thymus enlargement, largely due to thymocyte expansion. This has been attributed to the loss of the proapoptotic effects on thymocytes by adrenal GCs. Here, we test this concept and report that ACTH directly controls thymic growth post‐adrenalectomy (ADX) independent of the proapoptotic effect of GCs. This was supported by the finding that ADX caused thymus enlargement and a 1.7‐fold ( P < 0.001) increase in thymocyte number in GR LckCre mice resistant to GC‐induced thymocyte apoptosis, similar to the increase seen in wild‐type mice (2.2‐fold; P < 0.01). We show by immunostaining that melanocortin receptor subtype 2, which selectively binds ACTH, is partly expressed on the thymic epithelium. Furthermore, ACTH in comparison to vehicle induced a 2.0‐fold ( P < 0.01) increase in fetal thymic organ culture thymocyte numbers in vitro and enhanced 2.2‐fold ( P < 0.05) the expression of delta‐like ligand 4, a factor that supports T‐cell development. Additionally, adrenalectomized GR LckCre mice treated with ACTH under conditions that repressed endogenous ACTH secretion showed increased thymocyte cellularity (1.9‐fold; P < 0.01) and splenic naive T‐cell numbers (2.5‐fold; P < 0.001) compared to when treated with PBS. Altogether, our results show that ACTH directly controls thymocyte homeostasis independent of GCs. These results revise the old paradigm behind compensatory thymus growth following ADX, now demonstrating that ACTH has a central role in regulating thymocyte expansion when systemic GC concentration is low.—Talaber, G., Tuckermann, J. P., Okret, S. ACTH controls thymocyte homeostasis independent of glucocorticoids. FASEB J. 29, 2526‐2534 (2015). www.fasebj.org